The use of medical Marijuana in symptom management for cancer and other chronic patients - Kanari, Zinovia (Department of Nursing, Faculty of Health Sciences, Cyprus University of Technology, 2020)
Introduction: Medical cannabis or Medical marijuana has been used for a number of years as a complementary treatment to alleviate symptoms caused by cancer and other chronic diseases. Although this is one of the most controversial topics in medicine, in recent years it has caught the attraction of researchers to verify its safe administration. Aim: The aim of this study was to investigate the use of cannabis in the management of symptoms in people with cancer and other chronic diseases. Material and method: A review of literature has been conducted in most recent published articles from the past 3 years (2017-2020). The research was performed in the following databases: PubMed, Cinahl, Scopus and Google Scholar and the keywords used to filter the results were as follows: Medical Marijuana, symptoms management, Pain management, oncology patients or cancer patients, inflammatory bowel diseases and multiple sclerosis. Results: In this study, 8 articles were included which met the predefined criteria. The majority of these articles found that medical marijuana had positive effects in symptom management especially in pain management, wellbeing as well as in spasticity, bleeding and diarrhea, in in patients with cancer and other chronic diseases. Despite this, the rates were not statistically significant; as a result, the beneficial properties of the use of medical marijuana have not been scientifically proved yet. Conclusions: The results of several studies have found that positive effects can be caused by using cannabis; however, it has not been accepted by the scientific community. That may have been attributed to the lack of clinical trials due to its legal status. Therefore, more research is needed to ascertain the use of cannabis in oncology and chronic patients.
Keywords: Medical marijuana; Symptoms management; Pain management; Oncology patients or cancer patients; Inflammatory bowel disease; Multiple sclerosis; Ιατρική μαριχουάνα; Διαχείριση συμπτωμάτων; Ογκολογικοί ασθενείς ή ασθενείς με καρκίνο; Διαχείρηση του πόνου; Φλεγμονώδεις παθήσεις εντέρου; Πολλαπλή σκλήρυνση